Talking about gender in 2001, in the family and at school - Hinojosa Pari, Zinaida (2001)
Gender: Incredibly, this word is very fashionable in all environments and spaces, and it is said that the concept of gender can be found in each of our daily actions; moreover, it was present since the beginning of humanity. But the difficulties for its understanding and implementation begin when we put the word equity before it, that is, "gender equity", which we define as complementary, equal opportunities, equal value of men and women, both united in the construction of a new world.